Assessment of Stroke Risk Based on The Stroke Risk Score Card (SRSC) in Female Social Group - Anna Kurnia (Journal of Nursing and Health, 2025)
Stroke is one of the leading causes of death and the primary cause of disability, ranking third in Indonesia after heart disease and cancer. Preventing stroke and managing its risk factors are crucial for maintaining health from the productive years through to old age. The Stroke Risk Score Card (SRSC) is a screening instrument designed to enhance awareness of stroke risk and reduce stroke incidence through assessment and recording of stroke risks. Early risk assessment can improve quality of life, reduce economic burden, and foster a more health-conscious and responsive community. The Community Service included 38 female participants; the majority of whom were over 45 years old. Measurement results indicated that most participants had high cholesterol levels (>200), were classified as overweight based on Body Mass Index (BMI) and exhibited a lack of physical activity. The SRSC assessment revealed a low stroke risk (10.5%), moderate stroke risk (55.3%), and high stroke risk (34.2%). Health examinations and stroke risk assessments provided an initial overview of the health status within the female social group (PKK).